Payment discounts and surcharges: The role of consumer preferences - Joanna Stavins; Huijia Wu (Federal Reserve Bank of Boston, 2017)
We use new data from the 2015 Diary of Consumer Payment Choice to analyze price discounts and surcharges based on the payment method used for transactions. We examine consumer preferences for specific payment instruments and test whether consumer demand for payment instruments is price elastic. Specifically, we test whether consumers are likely to deviate from their preferred methods in order to get a discount or to avoid a surcharge. We find that the occurrence of price incentives is low, but consumers who preferred other payment methods had an 11.7 percent probability of switching to cash because of cash discounts, after controlling for merchant category and dollar value of the transaction. Payment method choice is affected very strongly by consumer individual preferences, but steering by merchants may be effective under some circumstances. Both merchants' reluctance to offer price discounts and consumers' limited response to them lead to the low observed occurrences of such incentives.
Keywords: D03; D14; G02; 330; consumer payments; consumer preferences; merchant steering; discounts; surcharges